Vestibular Function and Hippocampal Volume in the Baltimore Longitudinal Study of Aging (BLSA) - Kamil, Rebecca J. (Otol Neurotol, 2018)
OBJECTIVE: This study evaluated whether reduced vestibular function in aging adults is associated with lower hippocampal volume. STUDY DESIGN: Cross-sectional study. SETTING: Baltimore Longitudinal Study of Aging (BLSA), a long-running longitudinal cohort study of healthy aging. PATIENTS: Eligible participants were age ≥ 60 years and had both vestibular physiological testing and brain MRI at the same visit. INTERVENTION: Vestibular function testing consisted of the cervical vestibular-evoked myogenic potential (cVEMP) to assess saccular function, ocular VEMP (oVEMP) to assess utricular function, and video head-impulse testing (VHIT) to assess the horizontal semicircular canal vestibulo-ocular reflex (VOR). MAIN OUTCOME MEASURE: Hippocampal volume calculated using diffeomorphometry. RESULTS: The study sample included 103 participants (range of 35–90 participants in sub-analyses) with mean (±SD) age 77.2 years (±8.71). Multivariate linear models including age, intracranial volume, sex, and race showed that 1μV amplitude increase of cVEMP was associated with an increase of 319.1 mm(3) (p=0.003) in mean hippocampal volume. We did not observe a significant relationship between oVEMP amplitude or VOR gain and mean hippocampal volume. CONCLUSIONS: Lower cVEMP amplitude (i.e. reduced saccular function) was significantly associated with lower mean hippocampal volume. This is in line with prior work demonstrating a link between saccular function and spatial cognition. Hippocampal atrophy may be a mechanism by which vestibular loss contributes to impaired spatial cognition in older adults. Future work using longitudinal data will be needed to evaluate the causal nature of the association between vestibular loss and hippocampal atrophy.